The adoption of electronic commerce: A cross-country study of influencing factors in small-and mediums-sized enterprises - Chong, Sandy; Ramaseshan, Balasubramani (IEEE, 2005)
This study surveys the perceptions and experiences of Australian and Singaporean small- and medium-sized enterprises (SMEs) in the adoption of Internet-based Electronic Commerce (EC) and proposes a framework of EC adoption for SMEs. With a sample of 115 small businesses in Australia and 42 small businesses in Singapore, preliminary results show that respondents' perception of Internet-based EC are predominantly positive. However, a further analysis was found that age of firm, complexity, compatibility, communication channel, communication amount, customer pressure, competitive pressure, and perceived governmental support make a significant contribution to explaining the extent to which EC is adopted in Australia. Interestingly, perceived governmental support was also regarded as relevant by Singaporean firms, but in opposite ways from Australian SMEs.